Feasibility of Estimation of Aortic Wave Intensity Using Non-invasive Pressure Recordings in the Absence of Flow Velocity in Man - Hughes, Alun D.; Park, Chloe; Ramakrishnan, Anenta; Mayet, Jamil; Chaturvedi, Nish; Parker, Kim H. (Frontiers in Physiology, 2020)
Background Wave intensity analysis provides valuable information on ventriculo-arterial function, hemodynamics and energy transfer in the arterial circulation. Widespread use of wave intensity analysis is limited by the need for concurrent measurement of pressure and flow waveforms. We describe a method that can estimate wave intensity patterns using only non-invasive pressure waveforms, and its reproducibility. Methods Radial artery pressure and left ventricular outflow tract (LVOT) flow velocity waveforms were recorded in 12 participants in the Southall and Brent Revisited (SABRE) study. Pressure waveforms were analysed using custom-written software to derive the excess pressure (Pxs) which was compared with the LVOT flow velocity waveform, and used to calculate wave intensity. In a separate study, repeat measures of wave intensity and other wave and reservoir parameters were performed on 34 individuals who attended 2 clinic visits at an interval of approximately 1 month to assess reproducibility and reliability of the method. Results Pxs waveforms were similar in shape to aortic flow velocity waveforms and the time of peak Pxs and maximum aortic velocity agreed closely (mean difference = 0.00 (limits of agreement -0.02, 0.02)s). Wave intensity patterns when scaled to peak LVOT velocity gave credible estimates of wave intensity similar to values reported previously in the literature. The method showed fair to good reproducibility for most parameters. Conclusions The Pxs is a surrogate of LVOT flow velocity allowing estimation of aortic wave intensity with acceptable reproducibility. This enables widespread application of wave intensity analysis to large studies.